Shadow economy and financial sector development in Malaysia - Habibullah, Muzafar Shah; Din, Badariah; Saari, Mohd Yusof; Abdul Hamid, Baharom (EconJournals, 2016)
This paper explores the link between the shadow economy and financial sector development in Malaysia for the period 1971-2013. We calculate the size of the shadow economy by using the modified-cash-deposits-ratio (MCDR) approach recently developed by Pickhardt and Sardia (2011). We investigate the contention made by Blackburn et al. (2012) that financial sector development can mitigate shadow economy – higher level of financial sector development lead to lower level of shadow economy. Our results show that there is a non-linear long-run relationship between shadow economy and financial sector development in Malaysia, an inverted-U shape curve, suggesting that at lower (higher) level of financial sector development commensurate with higher (lower) level of the shadow economy. One policy implication from this study is that the financial sector can play an important role in reducing shadow economy by improving the accessibility to financing and to the credit market.